2018
DOI: 10.1111/cas.13706
|View full text |Cite
|
Sign up to set email alerts
|

UNC119 is a binding partner of tumor suppressor Ras‐association domain family 6 and induces apoptosis and cell cycle arrest by MDM2 and p53

Abstract: Ras‐association domain family 6 (RASSF6) is a tumor suppressor that interacts with MDM2 and stabilizes p53. Caenorhabditis elegans unc‐119 encodes a protein that is required for normal development of the nervous system. Humans have 2 unc‐119 homologues, UNC119 and UNC119B. We have identified UNC119 as a RASSF6‐interacting protein. UNC119 promotes the interaction between RASSF6 and MDM2 and stabilizes p53. Thus, UNC119 induces apoptosis by RASSF6 and p53. UNC119 depletion impairs DNA repair after DNA damage and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…As the interaction with UNC119Aa was weaker than that with UNC119Ab, we focused on UNC119Ab. UNC119B, which was previously demonstrated not to bind RASSF6, interacted with KRASB G12V (22). Therefore, it is unlikely that RASSF6 is involved in the interaction between KRASB G12V and UNC119A.…”
Section: Unc119a Interacts With Krasmentioning
confidence: 80%
See 4 more Smart Citations
“…As the interaction with UNC119Aa was weaker than that with UNC119Ab, we focused on UNC119Ab. UNC119B, which was previously demonstrated not to bind RASSF6, interacted with KRASB G12V (22). Therefore, it is unlikely that RASSF6 is involved in the interaction between KRASB G12V and UNC119A.…”
Section: Unc119a Interacts With Krasmentioning
confidence: 80%
“…We previously reported that UNC119A promotes the binding of RASSF6 to MDM2 (22). We also reported that the RA domain of RASSF6 binds to MDM2 and triggers apoptosis by stabilizing p53 (32).…”
Section: Unc119ab Promotes the Binding Of Rassf6 To Mdm2 Via Krasmentioning
confidence: 87%
See 3 more Smart Citations